The Influence of Financial Technology (Fintech) on the Financial Performance of Islamic Banking (Study on Islamic Banking listed on the Indonesia Stock Exchange Period 2016-2020) - Anindyastri, Ranty; Lestari, Wuryaningsih Dwi; Sholahuddin, Muhammad (Benefit: Jurnal Manajemen dan Bisnis, 2022)
The rapid technology development in Indonesia has an impact on the existence of various technological innovations, one of them is the financial sector. Financial technology is a technological innovation in the financial sector. The existence of financial technology is expected to be able to improve the performance of financial institutions so they can provide services to their customers more efficiently. This study aims to determine the influence of mobile banking, internet banking, and SMS banking on the financial performance of Islamic banking projected with Return on Assets (ROA). This study uses data in the form of annual financial statements of Islamic Banks listed on the Indonesia Stock Exchange in the period 2016-2020. This study sample was selected using purposive sampling techniques so as to obtain samples of Bank Aladin Syariah (Bank Maybank Syariah), Bank BNI Syariah, Bank BTPN Syariah, Bank BRI Syariah, Bank Mandiri Syariah, and Bank Panin Dubai Syariah. The study used regression analysis of panel data with EVIEWS 10 software. The results of this study show that mobile banking has a positive and significant influence on the financial performance of Islamic banking. While internet banking and SMS banking have a negative and insignificant influence on the financial performance of Islamic banking.